Misperception of the Implementation of the Principle of Restorative Justice to the Crime of Rape - Janur, Nur Akifah; Rahman, Abdul; Ardiansyah, Ardiansyah (Institut Agama Islam Negeri (IAIN) Kendari, 2023)
The concept of Restorative Justice is an alternative settlement of criminal cases in which, in criminal justice procedures, the focus of punishment is shifted to a mediation or deliberation process involving several parties, including the perpetrator, victim, family of the perpetrator or victim, and other related parties, where the principle of one crime in the Criminal Code (KUHP) is the crime of rape regulated in Article 285 of the Criminal Code which is a form of crime against decency. The purpose of the research is to review the perception errors in the application of the principles of restorative justice to the crime of rape to provide a direction for change regarding the principles of restorative justice in the crime of rape. The study comes to the conclusion that restorative justice must prioritize ensuring the rights of rape victims are upheld rather than being applied in a way that reconciles the victim and the offender. The TPKS Law, which governs rape law enforcement in Indonesia, ensures that victims' rights are protected in terms of handling rights, protection issues, and recovery rights. The punishment meted out to those who commit the crime of rape is a way of holding them accountable for their deeds.